Pendistribusian Dana Zakat Sebagai Upaya Pemberdayaan Ekonomi Umat Pada BAZNAS Kota Pasuruan - Khasanah, Irodatul; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2019)
This research is a qualitative research which aims to determine the distribution model of zakat funds in community economic empowerment at the Pasuruan City National Amil Zakat Agency. From the results of the research conducted it can be concluded that the process of distributing zakat funds in the economic empowerment of the people of BAZNAS in Pasuruan is an empowerment program, namely the Pasuruan Peduli, Pasuruan Makmur, Pasuruan Cerdas, and Pasuruan Bertaqwa. In terms of mustahiq income every month, mustahiq expenditures which include food ingredients, and other needs are above the average, in this case the standard of living mustahiq can be said to be prosperous.